Occurrence and morphometry of the hypopharyngeal glands in Scaptotrigona postica Lat. (Hymenoptera, Apidae, Meliponinae) - Costa, RAC; Cruz-Landim, C. (Indian Academy Sciences, 1999)
As compared to Apis mellifera where only workers have hypopharyngeal glands, in Scaptotrigona postica, these glands occur in workers, queens and males. They are composed of two long axial ducts with many unicellular secretory alveoli interconnected by secretory canaliculi. The axial ducts are longer in miles than in workers, but the alveolar areas of queens and males are generally smaller. In workers the alveoli have their greatest size in the nurses or middle-aged individuals while in queens and males they are larger in newly emerged individuals. The results indicate that the glands in workers may produce food for the brood as in A. mellifera, since they are well developed in the nurse workers. However, the function of the glands in queens and males remains to be clarified since these individuals have no part in brood care.
Keywords: morphology; morphometry; hypopharyngeal glands; Apidae